Hyperspectral optical coherence tomography for in vivo visualization of melanin in the retinal pigment epithelium. Issue 12 (13th August 2019) - Harper, Danielle J.; Konegger, Thomas; Augustin, Marco; Schützenberger, Kornelia; Eugui, Pablo; Lichtenegger, Antonia; Merkle, Conrad W.; Hitzenberger, Christoph K.; Glösmann, Martin; Baumann, Bernhard
Abstract: Previous studies for melanin visualization in the retinal pigment epithelium (RPE) have exploited either its absorption properties (using photoacoustic tomography or photothermal optical coherence tomography [OCT]) or its depolarization properties (using polarization sensitive OCT). However, these methods are only suitable when the melanin concentration is sufficiently high. In this work, we present the concept of hyperspectral OCT for melanin visualization in the RPE when the concentration is low. Based on white light OCT, a hyperspectral stack of 27 wavelengths (440‐700 nm) was created in post‐processing for each depth‐resolved image. Owing to the size and shape of the melanin granules in the RPE, the variations in backscattering coefficient as a function of wavelength could be identified—a result which is to be expected from Mie theory. This effect was successfully identified both in eumelanin‐containing phantoms and in vivo in the low‐concentration Brown Norway rat RPE. Abstract : The exact role of melanin in the retinal pigment epithelium (RPE) is still under debate. In recent years, optical techniques based on absorption and depolarization have been used for visualization of melanin in the RPE to try to solve some of these open questions. However both of these techniques rely on the melanin concentration to be sufficiently high. In this work, we have developed a hyperspectral extension to optical coherence tomography to visualize melanin in low concentrations, as is the case in the Brown Norway rat RPE.